A yoga & exercise randomized controlled trial for vasomotor symptoms: Effects on heart rate variability. (June 2016) - Jones, Salene M.W.; Guthrie, Katherine A.; Reed, Susan D.; Landis, Carol A.; Sternfeld, Barbara; LaCroix, Andrea Z.; Dunn, Andrea; Burr, Robert L.; Newton, Katherine M.
Highlights: A randomized controlled trial of exercise, yoga and usual activity was conducted. Post- or peri-menopausal women participated in the trial. Heart rate variability, an autonomic nervous system function measure, was examined. Heart rate variability did not differ between usual activity and yoga or exercise. Abstract: Objectives: Heart rate variability (HRV) reflects the integration of the parasympathetic nervous system with the rest of the body. Studies on the effects of yoga and exercise on HRV have been mixed but suggest that exercise increases HRV. We conducted a secondary analysis of the effect of yoga and exercise on HRV based on a randomized clinical trial of treatments for vasomotor symptoms in peri/post-menopausal women. Design: Randomized clinical trial of behavioral interventions in women with vasomotor symptoms (n = 335), 40–62 years old from three clinical study sites. Interventions: 12-weeks of a yoga program, designed specifically for mid-life women, or a supervised aerobic exercise-training program with specific intensity and energy expenditure goals, compared to a usual activity group. Main outcome measures: Time and frequency domain HRV measured at baseline and at 12 weeks for 15 min using Holter monitors. Results: Women had a median of 7.6 vasomotor symptoms per 24 h. Time and frequency domain HRV measures did not change significantly in either of the intervention groups compared to the change in the usual activity group. HRV results did not differ when the analyses were restricted to post-menopausal women. Conclusions: Although yoga and exercise have been shown to increase parasympathetic-mediated HRV in other populations, neither intervention increased HRV in middle-aged women with vasomotor symptoms. Mixed results in previous research may be due to sample differences. Yoga and exercise likely improve short-term health in middle-aged women through mechanisms other than HRV.